The Use Of E-Payment Method Toward Customer Satisfaction - Wahid Wahid; Ahmad Farhan; Oktavianty Oktavianty (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
The rise of electronic transaction have become more innovative over the year, starting from withdrawing money from atm to cashless transaction using mobile phone, the existence of physical money have been reduced for convenience. E-Payment have become one of many forms of cashless transaction, e-payment or electronic payment have been applicate by many big company especially food franchise. The e-payment known for its flexibility, especially form of e-payment can now be done using mobile phone which have no longer needed for a physical card. This convenience of usage has of course created satisfaction and dissatisfaction, which are determine by technology readiness. It can’t be denied that there are people who prefer physical payment than e-payment. These people were usually people who having a difficulty in using technology such as elder person or people that are living on rural areas. The purpose of paper is to explore how the use of e-payment have create satisfaction among customer and what are the reason of customer that prefer physical payment. The result of this paper indicate that the use of e-payment indeed create satisfaction among customer, this result supported by customer statement about flexibility and less risk of having not enough money or the possibility of losing money